The effect of mentoring on knowledge and implementation of my plate in adults - Karina, Sa'diah Multi; Pritasari; Damayanti, Didit; Rabbani, Fairuz Dhia (International Journal Of Community Medicine And Public Health, 2023)
Background: The prevalence of non-communicable diseases (NCDs), including hypertension and cancer, in Indonesia had increased, as shown by the result of Riskesdas 2018. To prevent the increase in the prevalence of NCDs, it is recommended to implement a healthy lifestyle in accordance with Indonesia balanced nutrition guidelines, including my plate. This study aimed to see the effect of nutrition education and mentoring on knowledge and implementation of my plate among adults. Methods: This study used non-equivalent quasi experimental design. Respondents were 60 adults who were divided into control and treatment groups with 4 weeks of treatments. Results: The age of respondents were between 22 to 44 years old with most of them were female (66.7%) in the treatment group and male (56.7%) in the control group. After four weeks of treatments, there were significant increases in nutritional knowledge (p=0.001) in both groups, but the results of the independent t-test showed no differences between groups. The study also showed that the number of respondents with daily meals similar to my plate increased from 33.3 to 50% in both groups. However, the average body weight of respondents also increased after treatments, but they were insignificant (p>0.05). Conclusions: Nutrition education and mentoring can increase the nutritional knowledge of adults significantly. However, changing nutrient intake and body weight would take a longer time.